2013
DOI: 10.4111/kju.2013.54.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Penile Epidermal Cyst in a Patient With Augmentation Penoplasty

Abstract: A 44-year-old male patient who had undergone augmentation penoplasty 20 years previously presented with a slowly growing penoscrotal mass. The penile mass was excised totally and the pathologic diagnosis was an epidermal cyst. Epidermal cysts are benign disorders that can occur in any part of the body. However, an epidermal cyst as a late complication of augmentation penoplasty is extremely rare. We report this case of a penile epidermal cyst that developed after augmentation penoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Epidermoid cysts of the penis are mainly encountered in children and they are very rare among elderly patients [3, 4]. Epidermoid cysts are common benign tumors that may arise from the infundibular portion of the hair follicles spontaneously or subsequent to trauma [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidermoid cysts of the penis are mainly encountered in children and they are very rare among elderly patients [3, 4]. Epidermoid cysts are common benign tumors that may arise from the infundibular portion of the hair follicles spontaneously or subsequent to trauma [5].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of congenital epidermoid cysts is unknown but it has been suggested that it may represent a monolayer teratoma of germ cell origin or abnormal embryologic closure of the median raphe [2]. In previously published articles, penile epidermoid cystic lesions have been reported as slow-growing, solitary, well-demarcated cystic lesions with a smooth and soft appearance and, when properly removed, they are not recurrent [3]. To the best of our knowledge, epidermoid cyst following distal hypospadias surgery is very rarely encountered.…”
Section: Introductionmentioning
confidence: 99%
“…2b-f; red arrowhead). [5][6][7][8] Almost of all these findings of epidermal cysts were extremely similar to the B-mode image of MTS.…”
mentioning
confidence: 75%
“…The classical Kaposi's sarcoma usually affects the lower legs of elderly males. Rare cases of penile affection have been observed …”
Section: Malignant Tumoursmentioning
confidence: 99%